2003
DOI: 10.1136/ard.62.7.651
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Y chromosome microchimerism with disease activity in patients with SLE: analysis of preliminary data

Abstract: Background: Recently it has been suggested that microchimerism may have a significant role in the aetiopathogenesis of some autoimmune diseases. Objectives: To evaluate the incidence of microchimerism in systemic lupus erythematosus (SLE), to quantify the phenomenon, to evaluate changes of microchimerism during follow up, and to correlate these data with clinical and laboratory variables. Methods: Patients were selected for the study on the basis of the following criteria: (a) pregnancy with at least one male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 26 publications
2
47
0
5
Order By: Relevance
“…However, the hypothesis that microchimerism was just a bystander in a process triggered by other mechanisms is also possible [127]. Although such findings could not be duplicated in a study of female patients with SLE [128], it does not rule out the possibility that microchimerism may play an important role in the complex pathogenesis of ADs.…”
Section: Microchimerismmentioning
confidence: 70%
“…However, the hypothesis that microchimerism was just a bystander in a process triggered by other mechanisms is also possible [127]. Although such findings could not be duplicated in a study of female patients with SLE [128], it does not rule out the possibility that microchimerism may play an important role in the complex pathogenesis of ADs.…”
Section: Microchimerismmentioning
confidence: 70%
“…Patient disease severity was not described in this study. In SLE, fetal cell microchimerism might be more likely to be found in affected tissues of severe cases (for example with nephritis) rather than benign ones (Mosca et al, 2003). Fetal cells thus probably do not trigger the disease but instead home to the affected maternal tissue if the damage reaches a particular 'threshold'.…”
Section: Do Fetal Cells Cause Autoimmune Disease?mentioning
confidence: 99%
“…It was recently reported that the Y-chromosome DNA of fetus origin (maternal-fetal microchimerism) was found in the peripheral blood of female patients with lupus nephritis (Mosca et al 2003) and in the salivary glands and lungs of female patients with Sjögren's syndrome (Kuroki et al 2002). Our observations suggest that fetal cells not only enter the maternal circulation, but also comprise a proportion of differentiated renal cells, such as those of the extraglomerular mesangium and renal tubular epithelium.…”
Section: Discussionmentioning
confidence: 57%